Case Report: The Genetic Diagnosis of Duchenne Muscular Dystrophy in the Middle East - Alghamdi, Fouad; Al-Tawari, Asmaa; Alrohaif, Hadil; Alshuaibi, Walaa; Mansour, Hicham; Aartsma-Rus, Annemieke; Mégarbané, André (Frontiers in Pediatrics, 2021)
The timely and accurate genetic diagnosis of Duchenne muscular dystrophy (DMD) enables prompt initiation of disease management and genetic counseling and optimal patient care. Despite the existence of best practice guidelines for the diagnosis of DMD, implementation of these recommendations in different parts of the world is challenging. Here, we present 4 unique case studies which illustrate the different diagnostic pathways of patients with DMD in Middle Eastern countries and highlight region-specific challenges to achieving timely and accurate genetic diagnosis of DMD. A lack of disease awareness and consequential failure to recognize the signs and symptoms of DMD significantly contributed to the delayed diagnoses of these patients. Additional challenges included limited available funding for genetic testing and a lack of local specialist and genetic testing centers, causing patients and their families to travel vast distances for appointments in some countries. Earlier and more accurate genetic diagnosis of DMD in this region would allow patients to benefit from effective disease management, leading to improvements in health-related quality of life.